A Care Continuum of Immediate ART for Newly Diagnosed Patients and Patients Presenting Later to Care at a Federally Qualified Health Center in New Orleans. (26th March 2019) - Halperin, Jason; Conner, Katherine; Butler, Isolde; Zeng, Pu; Myers, Leann; Clark, Rebecca; Van Sickels, Nicholas
Abstract: Rapid-start, immediate antiretroviral therapy (ART) initiation is a novel intervention that leads to earlier viral suppression. Longer-term data is essential before supporting this strategy more widely. CrescentCare, a federally qualified health center in New Orleans, followed 195 patients who received same-day ART; here we present a continuum of care for immediate ART intervention.